Efektivitas Inquiry Learning Berbasis Video Interaktif Terhadap Minat Belajar: Studi Kuasi-Eksperimen - Hadi, Moh Rizwan; Ismail, M; Hudori, Ahmad; Herianto, Edy (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The integration of technology into instructional strategies has become essential in modern education, particularly to address the issue of low student motivation. This study aimed to examine the effectiveness of a video-assisted inquiry learning model in improving students’ interest in Civic Education. A quasi-experimental design with a nonequivalent pretest-posttest control group pattern was used. The study involved 176 eleventh-grade Social Science students divided into two groups: the experimental group received inquiry-based learning supported by video media, while the control group was taught using conventional methods. Data were collected through questionnaires and classroom observations, and analyzed using descriptive and inferential statistics via SPSS version 25 at a 5% significance level. The results indicated a significant increase in learning interest among students in the experimental group. The paired t-test yielded a significance value of 0.001 (p 0.05), confirming that the video-assisted inquiry learning model had a statistically significant effect on students’ learning interest. These findings support the use of inquiry-based learning integrated with interactive video media to enhance student engagement and motivation at the secondary education level.